The Influence of Training, Work Environment and Career Development on Work Motivation That Has an Impact on Employee Performance at PT. Suryamas Elsindo Primatama In West Jakarta - Endang Sugiarti (International Journal of Artificial Intelligence Research, 2022)
This study aims to determine the effect of training, work environment, career development on work motivation which has an impact on employee performance at PT. Suryamas Elsindo Primatama in West Jakarta. The method used is quantitative. The sampling technique used saturated sampling, which amounted to 127 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of the training research have a significant effect on work motivation by 31.0% and hypothesis testing is obtained t count > t table or (7.498 > 1.979) this is strengthened by a significance of 0.000 < 0.05. The work environment has a significant effect on work motivation by 41.1% and hypothesis testing is obtained t count > t table or (9.343 > 1.979) this is strengthened by a significance of 0.000 <0.05. Career development has a significant effect on work motivation by 29.6% and hypothesis testing is obtained t count > t table or (7.248 > 1.979) this is strengthened by a significance of 0.000 <0.05. Training, work environment and career development simultaneously have a significant effect on work motivation with the regression equation Y = 6.565 + 0.226X1 + 0.403X2 + 0.220X3, the value of determination is 52.3% and hypothesis testing is obtained F count > F table or (44.922 > 2.450), this is also reinforced with a significance of 0.000 < 0.05. Work motivation has a significant effect on employee performance by 36.4% and hypothesis testing is obtained t count > t table or (8.452 > 1.979) this is strengthened by a significance of 0.000 <0.05